Pelatihan Penyusunan Rencana Anggaran Pendapatan dan Belanja Koperasi dengan Metode Actual To Budget+ - Sugiyanto, Sugiyanto (LPPM Universitas Koperasi Indonesia, 2025)
In practice of preparing Cooperative Income and Cost Budget Plans (RAPBK) there are still many inconsistencies between the methods used and their utilization. This condition needs to be resolved through a training approach for cooperative managers such as board of directors, supervisors, managers and finance. The training uses an adult training approach by prioritizing two-way communication and practice. The results of the training, apart from preparing material for preparing the RAPBK using actual methods up to budget +, have also made participants aware of how important the RAPBK is for cooperative managers as work guidelines, prioritizing fund allocation and business control and being able to provide feedback for each operational stage of the cooperative business. The basis for cooperative financial management is the RAPBK to direct the achievement of the cooperative's goals and desires.